Les juristes en épistoliers - Xavier Prévost (Clio@Themis)
The study of two hundred and eighty-three letters addressed to Joseph-Juste Scaliger shows the extent of the humanist’s legal network and the active contribution of forty-nine jurists to the Republic of Letters. This encyclopedic contribution is based on philology as a central knowledge, in line with Scaliger’s interests. As for law, its place – without being negligible – remains peripheral in this correspondence, while varying according to the regularity of the legal practice of each letter writer.